International economic reform : collected papers of Emile Despres - Meier, Gerald M. (New York : Oxford University Press, 1973)
This book is collection of the work of Emile Despres. The first two papers of the collection raise questions in connection with Britain's and Germany's foreign exchange policies that must yet be settled if there is to be progress toward international equilibrium. The second paper, underscores the promising opportunity and urgent need for commercial arrangements that would achieve a genuine liberalization of trade and some modifications of international financial and monetary arrangements.
Includes bibliographical references and index.
ne 24/01/2019
Loans
Keywords: Economic development; International economic relations; International finance